Prospects of training of professional managers of preschool education in XXI century: the demands today - Tetiana Krynytska (Vasyl Stefanyk Precarpathian National University, 2017)
The article highlights the relevance of training professional managers of pre-school education as specialists in management, which by the level of training to be able to withstand the competition in the market of educational services. Identified the importance of forming the heads of educational institutions, professional competence, personal qualities and strong knowledge of management, the transition to a qualitatively new level of management. Due to the basic ways of formation of professional competence of Heads of educational institutions. Key words: Manager-Professional, managerial skills, educational management, professional training, competence.